The Role of Moroccan Salafist Radicalism in Creating a Threat to Spain’s Security - Stanisław Kosmynka (Ksiegarnia Akademicka Publishing, 2021)
The paper is focused on the mechanisms and manifestations of Moroccan jihadism in Spain. It analyses how fighting Salafist radicalism from Mahgreb emerged in Spain and how it created challenges and threats for the security of the country. Europe has become one of the key fields of battle in the global war on jihadist terror. Today, in the age of decentralized terrorism, Al‑Qaeda is seen as a symbol of extremism legitimizing the use of violence by religious references. Jihadist ideology inspires the phenomenon of home‑grown terrorism in many European countries. The paper shows the background of the activity of some radical groups and movements in Morocco and then explains the ways it came to Spain. Moroccan jihadists played an increasingly important role in the activity of different Salafist cells in Spain. The article analyses the causes of the bomb attack carried out on 11 March 2004 in Madrid, which constituted an expression of open forms of terrorism, and the forms and factors of jihadist radicalism over the following years. It shows the links of the Moroccan Salafist movement with Islamic immigrant communities in Spain.